Exploring the Contributions of a Yoga Practice to Counsellor Education - Pittoello, Sarah R. (Canadian Journal of Counselling and Psychotherapy, 2016)
Students in a master’s of education counselling program were offered an ashtanga vinyasa yoga course, and were asked to explore their experience with and the perceived outcomes of engaging in a yoga practice. Data were collected using surveys, focus groups, and indepth interviews within a qualitative framework. Nine participants described the contribution of a yoga practice through three themes: structure and support, present-centred experience, and personal and professional benefits. These themes provide a model for considering how contemplative practices may serve counsellor education. The value of an embodied, contemplative practice in counsellor training, the importance of having an experienced yoga teacher, and further research are discussed.